Nasopharyngeal diffuse large B-cells lymphoma causing acute airway obstruction amid COVID-19 crisis: an anaesthetist’s nightmare - Yeap, Boon Tat; Teah, Ming Kai; Quay, Yen Ju Joanne; Wong, Melvin Teck Fui Wong (BMJ Publishing Group Limited, 2021)
Acute stridor is often an airway emergency. We present a valuable experience handling an elderly woman who was initially treated as COVID-19 positive during the pandemic in November 2020. She needed an urgent tracheostomy due to nasopharyngeal (NP) diffuse large B-cell lymphoma causing acute airway obstruction. Fortunately, 1 hour later, her NP swab real-time PCR test result returned as SARS-CoV-2 negative. This interesting article depicts the importance of adequate preparations when handling potentially infectious patients with anticipated difficult airway and the perioperative issues associated with it.